Resveratrol and curcumin synergistically induces apoptosis in cigarette smoke condensate transformed breast epithelial cells through a p21Waf1/Cip1 mediated inhibition of Hh-Gli signaling. (September 2015) - Mohapatra, Purusottam; Satapathy, Shakti Ranjan; Siddharth, Sumit; Das, Dipon; Nayak, Anmada; Kundu, Chanakya Nath
Highlights: Resveratrol+ curcumin synergistically caused apoptosis in MCF-10A-Tr cells. Res facilitated Cmn uptake in MCF-10A-Tr cells. Resveratrol+ curcumin induced apoptosis through inhibition of Hh-Gli signaling. Resveratrol+ curcumin inhibits of Hh-Gli components in p21 Waf1/Cip1 dependent manner. Abstract: Combination therapy using two or more small molecule inhibitors of aberrant signaling cascade in aggressive breast cancers is a promising therapeutic strategy over traditional monotherapeutic approaches. Here, we have studied the synergistic mechanism of resveratrol and curcumin induced apoptosis using in vitro (cigarette smoke condensate mediated transformed breast epithelial cell, MCF-10A-Tr) and in vivo (tumor xenograft mice) model system. Resveratrol exposure increased the intracellular uptake of curcumin in a dose dependent manner and caused apoptosis in MCF-10A-Tr cells. Approximately, ten fold lower IC50 value was noted in cells treated with the combination of resveratrol (3 μM) and curcumin (3 μM) in comparison to 30 μM of resveratrol or curcumin alone. Resveratrol + curcumin combination caused apoptosis by increasing Bax/Bcl-xL ratio, Cytochrome C release, cleaved product of PARP and caspase 3 in cells. Interestingly, this combination unaltered the protein expressions of WNT-TCF and Notch signaling components, β-catenin and cleaved notch-1 val1744, respectively. Furthermore, the combination also significantly decreased the intermediates of Hedgehog-Gli cascade including SMO, SHH, Gli-1, c-MYC, Cyclin-D1, etc. and increased the level of p21 Waf/Cip1 in vitro and in vivo. A significant reduction of Gli- promoter activity was noted in combinational drug treated cells in comparison to individual drug treatment. Un-alteration of the expressions of the above proteins and Gli1 promoter activity in p21 Waf/Cip1 knockout cells suggests this combination caused apoptosis through p21 Waf/Cip1 . Thus, our findings revealed resveratrol and curcumin synergistically caused apoptosis in cigarette smoke induced breast cancer cells through p2  Waf/Cip1 mediated inhibition of Hedgehog-Gli cascade.